Hubungan Antara Pengetahuan Ibu Tentang Garam Beryodium Dan Pola Konsumsi Zat Goitrogenik Terhadap Kadar Ekskresi Yodium Urin Siswa Sdn 4 Krebet Kecamatan Jambon Kabupaten Ponorogo - Roselia Nugraha, Agrivin, Muwakhidah, SKM, M.Kes (2016)
Iodine Deficiency Disorders (IDD) is one of the nutritional problems are factors that inhibit the development of human resources as it can cause disruption of mental development and intelligence, especially in children. Severity of endemicity of a region other than the assessed based on the enlargement of the thyroid gland, also can assess the median iodine content in urine or Urine Excretion of Yodiun (UEY). UEY describes iodine's intake, because 90% of iodine that enter the body through the urine is excreted. This study was conducted to determine the correlation of mother's knowledge on iodized salt and consumption patterns goitrogenik substance on levels of UEY's Elementary School 4 students Krebet Jambon Ponorogo. This study uses observational analytic with cross sectional approach. Sampling by using random sampling, the total of research subjects is 33 respondents. The data was collected by interview using questionnaire and urine sampling using spectophotometric method and the datum were analyzed by using Pearson Product Moment. The percentage of the highest maternal knowledge is less knowledge, amounting to 51.5%, the percentage of goitrogenik consumption of> 10mg / hr is 75.8% and the percentage UEY's levels of 100-199 mg / l is 57.6%. There is a significant correlation between the level of mothers' knowledge of iodized salt on levels of UEY's Elementary School 4 students (p = 0.028; r = -0.382). There is a significant correlation between the consumption of goitrogenik substance on levels of UEY's Elementary School 4 students Krebet (p = 0.002; r = 0.526). of mother's knowledge on iodized salt and consumption patterns goitrogenik substance is correlated with levels of UEY's Elementary School 4 students Krebet Jambon Ponorogo.